Analysis of Brand Credibility to Brand Reputation in Indomie Case Study - Rafdi, Abi; Irawan, Bangbang; Yuliana, Lingga (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
This study aims to analyze the relationship between brand credibility and brand reputation in the Indomie case study. The research method chosen by the author is a type of quantitative research. The sampling technique uses purposive sampling. A total of 130 respondents were involved in this study. The respondents were men and with an age range of 17-57 years and domiciled in Greater Jakarta and consumers of Indomie products. The data source uses primary data by distributing questionnaires through the intermediary of Google Forms. Closed questions were used in this study. The data analysis technique uses Partial Least Square using the SmartPLS tool version 4.1.0.0. The first hypothesis suggests that brand credibility has a positive effect on brand reputation. The management implications of this research include the need for the Indomie brand to be able to respond to customers promptly. The answer manifests itself in product concerns addressed and in innovations produced by firms that keep up with consumer preferences. It will give brand owners excellent reputation to be eaten for a long time if they respond to the current response. In order to prevent customers from considering trying other products because well-known brands consistently cater to their needs.